2015
DOI: 10.1080/17448689.2015.1009695
|View full text |Cite
|
Sign up to set email alerts
|

Myths and Traditions as Constraints or Resources? Path Dependency and Decoupling Strategies among Civil Society Organizations

Abstract: History and traditions are important for many civil society organizations (CSOs). However, CSOs have to mediate between their original mission and modern-day realities. This article argues that understanding the concept of decoupling can enrich analyses of how organizations deal with path dependency. Hence, this article discusses cross-fertilization between historical and organizational institutionalism. This is illustrated through a study of Swedish CSOs using survey data, interviews and documents. The Swedis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The popular movement format in fact became so dominant in Sweden during the twentieth century that most membership-based organizations in other fields also self-identified as ''movements'' and organized themselves according to the movements' signum federative structure(cf. Micheletti 1995;Å berg 2015).…”
mentioning
confidence: 99%
“…The popular movement format in fact became so dominant in Sweden during the twentieth century that most membership-based organizations in other fields also self-identified as ''movements'' and organized themselves according to the movements' signum federative structure(cf. Micheletti 1995;Å berg 2015).…”
mentioning
confidence: 99%
“…Each respondent was interviewed twice, informed by literature on resource mobilisation of organizational resources and institutional context and pressures (Åberg, 2015;Barney, 1991;Bekkers, 2005;Chambré, 1997;Desa, 2012;Pfeffer & Salancik, 1978;Sherer & Lee, 2002), the volunteering literature (Brudney & Meijs, 2009;Handy et al, 2010;Hustinx et al, 2010;Shin & Kleiner, 2003;Wilson, 2012), the literature on Russian civil society developments (Crotty, 2009;Fröhlich, 2012;Henry, 2006Henry, , 2010Jakobson & Sanovich, 2010;Sundstrom, 2005;Thomson, 2006), and commentary on volunteering in the Russian Federation and the impact of Soviet cultural antecedents (Howard, 2002;Mishler & Rose, 1997;Petukhov, 2006Petukhov, , 2008Smolar, 1996). The second interview was complemented with questions arising from the observations conducted.…”
Section: Methodsmentioning
confidence: 99%
“…While not focusing on policy professionals, earlier research on demands for the efficacy and professionalization of CSOs in Scandinavia has suggested that organizations tend to deal with these demands by relying on external expertise from, for example, think tanks, external consultants, and PR firms (öberg & Svensson 2012;Åberg, einarsson & Reuter 2021). another way of dealing with conflicting demands within CSOs has been to use decoupling practices (Åberg 2013, 2015arvidson & Lyon 2014;Heras-Saizarbitoria 2014;Brandtner 2021). It has also been demonstrated that conflicts between the roles of members and paid staff (e.g., Fries 2011; Karlberg 2019) are especially prominent in metaorganizations (ahrne & Brunsson 2008).…”
Section: Professionalization and Membership In Civil Societymentioning
confidence: 99%
“…The myth concept is used to analyze how the logic of membership and membership-driven decision-making is handled by policy teams in large member-based CSOs (see also Åberg 2015). Just as highly generalized myths regarding, for instance, professionals, contracts, and expertise are important for modern organizations in general (Meyer & Rowan 1977:347), we understand the history of mass-movement organizations (especially in the "popular movement tradition") and member centrality as a powerful myth that modern member-based CSOs must relate to (see also Åberg 2015;Selle, Strømsnes, Svedberg et al 2018:44). an example of how this myth is upheld and activated is the democratic decision-making process involving the congress of members, annual general meetings, the board, and member meetings, a process that in theory grants members full governance of the organization.…”
Section: Institutional Theory and The Logic And Myth Of Membershipmentioning
confidence: 99%
See 1 more Smart Citation